Agronomic effectiveness of phosphate rock evaluated in soybean crop - Junior, Adilson de Oliveira; Prochnow, Luís Ignácio; Klepker, Dirceu (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the relative agronomic effectiveness of the application of broadcasted and banded phosphorus rates, testing a standard source (triple superphosphate) and Arad phosphate rock in a soybean crop, in the Balsas, MA, Brazil. The experiment was carried out in October 2004, on a Typic Hapludox, clayey texture and very low available phosphorus, conducted with soybean [Glycine max (L.) Merrill.], cultivar BRS Sambaíba], for three consecutive harvests (2004/2005 to 2006/2007). The third harvest was carried out on residual effect of the previous applications. In general, it was not observed any differences related to the localization of the standard source. In contrast, Arad phosphate rock localization reduced the relative agronomic effectiveness significantly. In the first two harvests, broadcasted Arad phosphate rock resulted in approximately 76% of relative agronomic effectiveness, showing medium agronomic viability. Under residual effect, banded triple superphosphate resulted in similar response to that obtained with annual application of triple superphosphate, however, the increase in relative agronomic effectiveness was greater when broadcasting both phosphorus sources.